Unsteady aerodynamic analysis and effectiveness of bio-inspired flapping wings in V-formation flight - Billingsley, Ethan; Ghommem, Mehdi; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar (SAGE Publications, 2022)
Several bird species have been observed to fly in V-formation, an arrangement which exploits aerodynamic features to allow the group to conserve energy when migrating over long distances without stopping and feeding. The use of such grouping arrangement and organized pattern has demonstrated longer endurance and less power consumption in comparison with single flights. In this work, a computationally efficient potential flow solver based on the unsteady vortex lattice method (UVLM) is employed to assess the aerodynamic performance of flapping wings in forward flight in terms of lift and thrust generation along with the propulsive efficiency. The UVLM has the capability to simulate incompressible and inviscid flows over moving thin wings where the separation lines are known a priori. A bio-inspired, albatross wing shape is considered and its aerodynamic performance in formation flights is compared against conventional elliptical and rectangular wing shapes. The aerodynamic analysis is carried out for different wing arrangements of 3-body and 5-body V-formations to determine the optimal spacing parameters leading to maximum propulsive efficiency. The simulation results reveal that, at the optimal formation angle and separation distance, the albatross-inspired wing shape produces the most lift over the flapping cycle, while the rectangular wing shape generates the most thrust over the flapping cycle. Furthermore, the optimal configuration in terms of propulsive efficiency is found to be a 5-body V-formation utilizing the albatross wing shape with a separation distance set to one-third of the span and a formation angle set to 139°. The present study provides guidance for the design of multi-flapping wing air vehicles based on the expected flight mission. The albatross wing shape is found to have superior capability in producing lift, while the elliptical wing shape is observed to consume less power. The rectangular wing shape is found to produce higher thrust and then can achieve faster forward motion.
Keywords: aerodynamic performance; bioinspiration; flapping wings; UVLM; V-formation flight